2000
DOI: 10.1046/j.1365-2222.2000.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional effects of the inhibition of the cysteine protease activity of the major house dust mite allergen Der p 1 by a novel peptide‐based inhibitor

Abstract: PTL11028 is a highly potent and selective irreversible inhibitor of the cysteine protease activity of Der p 1, an activity that may be modulated in vivo by some human cystatins. PTL11028 prevents the Der p 1-mediated cleavage of CD23 from human B cells and significantly reduces HDM-induced permeabilization of the epithelial barrier. PTL11028 is an important tool to examine the biological effects of Der p 1 in a range of in vitro and in vivo model systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
(61 reference statements)
0
31
0
Order By: Relevance
“…Our findings demonstrate that accumulated CRTH2 + CD4 + T H 2 memory cells are closely associated with DC-LAMP + DCs within dermis of lesional skin of AD, but not T H 1-mediated inflammatory skin diseases, suggesting that TSLP-DCs may interact with CRTH2 + CD4 + T H 2 effector memory cells and induce their further T H 2 polarization at the inflammatory sites, thereby contributing to the maintenance and relapse of T H 2-mediated allergic diseases. These in vivo observations were further substantiated by the findings that signals from TSLP-DCs are the most effective on upregulation of genes involved in T H 2 polarization, such as CRTH2, GATA-3, c-MAF, and IL17RB (Fort et al, 2001;Matsuoka et al, 2000), as well as genes encoding the proteins that are found in epithelial cells, eosinophils, basophils, or antigen-presenting cells during allergic inflammation, including the T H 2-attracting chemokine TARC, cystatin A (John et al, 2000), CharcotLeydon crystal protein (Golightly et al, 1992;Ackerman et al, 1993), and prostaglandin D2 synthase. Our findings broaden the understanding of heterogeneous T H 2 cells that are not only the principal producers of T H 2 cytokines but also capable of producing other effective molecules to trigger allergic inflammation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our findings demonstrate that accumulated CRTH2 + CD4 + T H 2 memory cells are closely associated with DC-LAMP + DCs within dermis of lesional skin of AD, but not T H 1-mediated inflammatory skin diseases, suggesting that TSLP-DCs may interact with CRTH2 + CD4 + T H 2 effector memory cells and induce their further T H 2 polarization at the inflammatory sites, thereby contributing to the maintenance and relapse of T H 2-mediated allergic diseases. These in vivo observations were further substantiated by the findings that signals from TSLP-DCs are the most effective on upregulation of genes involved in T H 2 polarization, such as CRTH2, GATA-3, c-MAF, and IL17RB (Fort et al, 2001;Matsuoka et al, 2000), as well as genes encoding the proteins that are found in epithelial cells, eosinophils, basophils, or antigen-presenting cells during allergic inflammation, including the T H 2-attracting chemokine TARC, cystatin A (John et al, 2000), CharcotLeydon crystal protein (Golightly et al, 1992;Ackerman et al, 1993), and prostaglandin D2 synthase. Our findings broaden the understanding of heterogeneous T H 2 cells that are not only the principal producers of T H 2 cytokines but also capable of producing other effective molecules to trigger allergic inflammation.…”
Section: Discussionmentioning
confidence: 76%
“…By contrast, TSLP-DCs do not induce the expression of genes encoding chemokines lymphotactin, MIP-1a, and MIP-1b, which are produced during T H 1-polarized inflammation (Ritz et al, 2004;Muller et al, 2003), and IFN-g, IL-18Rap, CCR5, and CD70, which are expressed by T H 1 or T EM cells. Interestingly, only TSLP-DCs induced CRTH2 + CD4 + T H 2 memory cells to express genes encoding cystatin A, Charcot-Leydon crystal protein, and prostaglandin D2 synthase, which are known to be selectively expressed by eosinophils and basophils (Golightly et al, 1992;Ackerman et al, 1993) and critical for allergic inflammation (John et al, 2000;Matsuoka et al, 2000), as well as chemokine TARC known to recruit T H 2 cells (Ritz et al, 2004) ( Figure 3B). These results suggest that TSLP-DCs not only maintain the central memory phenotype but also further strengthen the ''T H 2'' properties of CRTH2 + CD4 + T H 2 memory cells.…”
Section: T H 2 Progression Of Crth2 + Cd4 + T H 2 Memory Cells Inducementioning
confidence: 96%
“…Actually, it has been reported that a peptide-based inhibitor, PTL11028, showed inhibitory effects for the catalytic activities of group I mite allergens and improved airway hyperreactivity, inflammation, and systemic sensitization induced by Der p 1 in rats (40,41). Structural analyses of the interaction between SCCA/Der p 1 would give us a hint as to how to develop a novel low molecular weight compound to block the catalytic activity of group I mite allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Given their role in immune responses, it is perhaps not surprising that cystatins (e.g., cat Fel d3; Ichikawa et al, 2001), CPs (e.g., dust mite der P1; John et al, 2000, and references therein), and papain-related enzymes (Mansfield et al, 1985) can be potent allergens. Analysis of the above data argues for an intimate relationship between cystatins and regulation of the immune system.…”
Section: (3) Immunomodulationmentioning
confidence: 99%